Novel metaphor processing in young autistic children - Agustín Vicente; Elena Castroviejo; Ingrid Lossius Falkum; Isabel Martín-González; Kristen Frances Schroeder (Language Development Research, 2025)
The purpose of this study is to explore possible differences between autistic and neurotypical (NT) children in novel metaphor comprehension. Much of the recent literature has related metaphor comprehension difficulties that autistic individuals exhibit to general linguistic abilities. In our design, we carefully pair-matched young autistic children (3.13 to 12.25 years of age) toNT controls (3.69 to 9.04 years of age) on verbal mental age and tested their metaphor interpretation abilities with a picture selection paradigm combined with eye tracking measures. We predicted differences in performance in both types of measures, although we foresaw autistic participants performing above chance in the picture selection task. However, results did not show a difference between groups in the picture selection task, which would favor accounts that relate metaphor interpretation to linguistic abilities in autistic population. Interestingly, the eye tracking observations revealed differences between groups concerning gaze movements in the region corresponding to the processing of the metaphoric vehicle.  Such differences replicate those found in previous studies with similar designs, such as Vulchanova et al.’s (2019). On the other hand, the evidence presented and discussed in the paper does not suggest either impairment or delay with respect to metaphor processing. Rather, the evidence only suggests differences. While the source of such processing differences is still unknown, the results of the current study cast some doubts the idea that the main factor in metaphor processing in the autistic population is their structural language level.